ASSESSMENT OF LIPID PEROXIDATION PROCESSES AND LIPID METABOLISM DISORDERS IN PATIENTS WITH ISCHEMIC HEART DISEASE UNDERGOING COMBINED HYPOLIPIDEMIC THERAPY - Juraboyev X.O,; Tashtemirova I.M., (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In the 20th and 21st centuries, cardiovascular diseases (CVD), particularly complications associated with atherosclerosis, remain among the leading causes of death and disability. In many cases, ischemic heart disease (IHD) develops due to the combined influence of several risk factors, including increased levels of low-density lipoproteins (LDL) in blood serum. Genetic factors account for approximately 50% of LDL variability. The onset of IHD is influenced by a complex interaction of hemodynamic, neurohumoral, metabolic, and other factors [4,8,11].